Power of Product of Commuting Elements in Semigroup equals Product of Powers

From ProofWiki
Jump to navigation Jump to search

Theorem

Let $\struct {S, \circ}$ be a semigroup.

For $a \in S$, let $\circ^n a = a^n$ denote the $n$th power of $a$.

Let $a, b \in S$ such that $a$ commutes with $b$:

$a \circ b = b \circ a$


Then:

$\forall n \in \N_{>0}: \circ^n \paren {a \circ b} = \paren {\circ^n a} \circ \paren {\circ^n b}$

That is:

$\forall n \in \N_{>0}: \paren {a \circ b}^n = a^n \circ b^n$


Proof

The proof proceeds by the Principle of Mathematical Induction:


Let $\map P n$ be the proposition:

$\circ^n \paren {a \circ b} = \paren {\circ^n a} \circ \paren {\circ^n b}$


Basis of the Induction

\(\displaystyle \circ^1 \paren {a \circ b}\) \(=\) \(\displaystyle a \circ b\) Definition of $\circ^1$
\(\displaystyle \) \(=\) \(\displaystyle \paren {\circ^1 a} \circ \paren {\circ^1 b}\) Definition of $\circ^1$

So $\map P 1$ holds.


This is the basis for the induction.


Induction Hypothesis

Suppose that $\map P k$ holds:

$\map {\circ^k} {a \circ b} = \paren {\circ^k a} \circ \paren {\circ^k b}$

This is the induction hypothesis.

It remains to be shown that:

$\map P k \implies \map P {k + 1}$

That is, that:

$\map {\circ^{k + 1} } {a \circ b} = \paren {\circ^{k + 1} a} \circ \paren {\circ^{k + 1} b}$


Induction Step

\(\displaystyle \circ^{k + 1} \paren {a \circ b}\) \(=\) \(\displaystyle \paren {\map {\circ^k} {a \circ b} } \circ \paren {a \circ b}\) Definition of $\circ^{k + 1}$
\(\displaystyle \) \(=\) \(\displaystyle \paren {\paren {\circ^k a} \circ \paren {\circ^k b} } \circ \paren {a \circ b}\) Induction Hypothesis
\(\displaystyle \) \(=\) \(\displaystyle \paren {\circ^k a} \circ \paren {\paren {\paren {\circ^k b} \circ a} \circ b}\) $\circ$ is associative
\(\displaystyle \) \(=\) \(\displaystyle \paren {\circ^k a} \circ \paren {\paren {a \circ \paren {\circ^k b} } \circ b}\) Powers of Commuting Elements of Semigroup Commute
\(\displaystyle \) \(=\) \(\displaystyle \paren {\paren {\circ^k a} \circ a} \circ \paren {\paren {\circ^k b} \circ b}\) $\circ$ is associative
\(\displaystyle \) \(=\) \(\displaystyle \paren {\circ^{k + 1} a} \circ \paren {\circ^{k + 1} b}\) Definition of $\circ^{k + 1}$

So $P \left({k + 1}\right)$ holds.


Thus by the Principle of Mathematical Induction, the result holds for all $n \in \N_{>0}$:

$\forall n \in \N_{>0}: \map {\circ^n} {a \circ b} = \paren {\circ^n a} \circ \paren {\circ^n b}$

$\blacksquare$


Sources